Snow Day - Margaret McNamara (New York, NY, United States Simon Spotlight, 2007)
The kids in Mrs. Connor's class love the snow! And they love snow days even more! But when the snow will not stop falling, Nia realizes that staying at home is not so much fun after all.
Keywords: Level Readers